Modernizing Islam - Shaza Khan (International Institute of Islamic Thought, 2004)
As the political climate between many western and Muslim nations continues to intensify, the rhetoric of a “clash of civilizations” has reemerged in our news media, governments, and academic institutions. Muslims and non-Muslims, with varying political agendas, insist that Islam is inherently incompatible with modernity, democracy, and the West. Yet the contributors to Modernizing Islam: Religion in the Public Sphere in the Middle East and Europe demonstrate otherwise as they examine the (re)Islamization of Europe and the Middle East and reveal the ways in which “Islamic political activism” (p. 3), or Islamism, promotes modernization. In the first of three sections, “Issues and Trends in Global Re- Islamization,” François Burgat describes how the progressive components of Islamization get hidden under a myriad of misconceptions. The term Islamist, he asserts, often serves to essentialize Muslim political activists by depicting them as a homogenous group comprised of Islamic militants. The use of this term also “tends to strengthen the idea that Islamists are the only ones using … religion for political purposes” (p. 28), though clearly other individuals, institutions, and religious organizations use religion for political ends as well. Due to the essentialized and reductionist uses of the term, the real characteristics of Islamism as a “relative, plural, and reactive” phenomenon are rarely recognized (p. 18). These obscuring lenses blur the image(s) of Islam even more in a country like France, where issues related to religion are often relegated to the “irrational.” In such contexts, Islamist movements are constantly invalidated, though the activists’ reasons for opposition may well be rooted in legitimate political, economic, and social factors. The obscurants that Burgat details in chapter 1 often cause individuals to view Islamists as anti-modernist and retrogressively reactionary. Yet in chapter 2, “The Modernizing Force of Islam,” Bjorn Olav Utvik argues “that if Islamism is a reaction it is a progressive one, a step forward into something new, not trying to reverse social developments, but rather to adapt religion so that it enables people to cope with the new realities” (p. 60). Utvik links modernization to both urbanization and industrialization and characterizes it as a phenomenon that results in increased individualization, social mobilization, and recognition of state centrality in achieving political ends (p. 43). He then proceeds to draw parallels between the goals of Islamist movements and characteristics of modernization. In the next chapter, “Islam and Civil Society,” John Esposito further demonstrates Islam’s compatibility with modernization and, more specifically, with democracy. He surveys Tunisia, Algeria, Turkey, Egypt, Iran, and the Gulf states in an effort to illustrate the importance, functionality, and popularity of their Islamic organizations. Importantly, he asserts that while most of these Islamist movements begin by working within the fold of the governments’ established political processes, “the thwarting of a participatory political process by governments that cancel elections or repress populist Islamic movements fosters radicalization and extremism” (p. 92). Esposito suggests that increasing open competition for political power in these countries and sustaining a reexamination of traditional Islamic rulings regarding pluralism, tolerance, and women’s role in society will result in greater compatibility between Islam and democracy ...